Sovetskoi militsii -- 70 let . Sovetskoi militsii -- 70 let . Soviet Militia -- 70 Years . Советской милиции -- 70 лет - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Daily activities of the police in a historical perspective. Featured in the program: Voznesenskii, Lev Aleksandrovich (Political Columnist); Kazakov, V.A. (Investigator); Zhukov, V.I. (Head of the Juvenile Correctional Facility); Vlasov, Aleksandr Vladimirovich (Minister of Internal Affairs of the USSR) Contributors: Glavnaia redaktsiia propagandy (Studio) Передача посвящена сотрудникам правоохранительных органов. В программе участвуют: Вознесенский, Лев Александрович (Политический обозреватель); Казаков, В. А. (Следователь); Жуков, В.И. (Начальник воспитательной колонии); Власов, Александр Владимирович (Министр внутренних дел СССР) Создатели: Главная редакция пропаганды (Студия)